Pemanfaatan Bionanomaterial Chitosan Sebagai Adsorben Untuk Penyisihan Parameter Zat Organik Pada Pengolahan Air Gambut - Hasibuan, Nur Anisyah Handayani; Elystia, Shintia; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Nanomaterials are nano-sized materials that can be formed from several its forming compounds. This research uses chitosan as an adsorbent in peat water treatment located in Rimbo Panjang Village, Kampar. Chitosan obtained from shrimp shell waste, with several stages of the process first carried out, such as deproitenation, demineralization and deacetylization. Furthermore, the process of making chitosan bionanomaterial using magnetic stirer speed of 1200 rpm and added 2% acetic acid and 200 ml Tripolyphospate (1mg/mL). The solution is then filtered and dried using an oven at 120o C for 2 hours. The independent variable peat water treatment used in this study were adsorbent masses of 1,3,5 and 7 grams and stirring time of 30, 60, and 90 minutes. The final concentration obtained in the from of reduction in removal of organic matter at 5,878 mg/L with a percentage value of 98,67% at the mass of the 5 gram adsorbent with 30 minutes.Keywords: Bionanomaterial Chitosan, Adsorption. Peat Water.